Cervical surgery for ossification of the posterior longitudinal ligament: One spine surgeon's perspective - Epstein, Nancy E. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The selection, neurodiagnostic evaluation, and surgical management of patients with cervical ossification of the posterior longitudinal ligament (OPLL) remain controversial. Whether for prophylaxis or treatment, the decision to perform anterior vs. posterior vs. circumferential cervical OPLL surgery is complex. MR AND CT DOCUMENTATION OF OPLL: Together, MR and CT cervical studies best document the full extent of OPLL. While MR provides the optimal soft-tissue overview (e.g. hyperintense signals reflecting edema/myelomalacia in the cord), CT's directly demonstrate the ossification of OPLL often “missed” by MR (e.g. documents the single or double layer signs of dural penetration. PATIENT SELECTION: Patients with mild myelopathy/cord compression rarely require surgery, while those with moderate/severe myelopathy/cord compression often warrant anterior, posterior, or circumferential approaches. OPERATIVE APPROACHES: Anterior corpectomies/fusions, warranted in patients with OPLL and kyphosis/loss of lordosis, also increase the risks of cerebrospinal fluid (CSF) leaks (e.g. single/double layer sign), and vascular injuries (e.g. carotid, vertebral). Alternatively, with an adequate lordosis, posterior procedures (e.g. often with fusions), may provide adequate multilevel decompression while minimizing risk of anterior surgery. Occasionally, combined pathologies may warrant circumferential approaches. ANESTHETIC AND INTRAOPERATIVE MONITORING PROTOCOLS: The utility of awake nasotracheal fiberoptic intubation/awake positioning, intraoperative somatosensory/motor evoked potential, and electromyographic monitoring, and the requirement for total intravenous anesthesia (TIVA) for OPLL surgery is also discussed. CONCLUSION: Anterior, posterior, or circumferential surgery may be warranted to treat patients with cervical OPLL, and must be based on careful patient selection, and both MR and CT documentation of the full extent of OPLL.